Review of Mortality Patterns in Korle Bu Teaching Hospital's Emergency Department Over One Year (London Journal of Medical and Health Research, 2025)
Background: Mortality trends in Emergency departments serve as vital indicators of healthcare quality and system effectiveness. Understanding the mortality patterns in these settings is crucial for optimising emergency care delivery. However, limited research exists on mortality trends in emergency departments, particularly in low-resource settings such as Ghana. This study seeks to provide valuable insights into the factors contributing to mortality and inform strategies for improving emergency care.This study aimed to analyse mortality trends in the Emergency Department of Korle-Bu Teaching Hospital in Ghana over a specified period.Methodology: This retrospective study utilised data obtained from medical records of patients who presented to the emergency department of Korle-Bu Teaching Hospital and subsequently died during their hospital stay for the year 2023. Data on patient demographics, admission records, clinical characteristics, and diagnosiswere collected, analysed, and summarised using descriptive statistics.Results: During the review period, the total attendance at the KBTH Accident and Emergency Centre was 14,472, comprising 8,666 males and 5,806 females. Among these attendees, 5,856 individuals were admitted. The centre reported 492 cases of Brought-in-Dead (Dead on Arrival). The age group with the highest attendance was 15-44 years. A total of 909 deaths occurred in the emergency department, with 465 males and 444 females. The age distribution of fatalitiesshowed the majority occurring in the 60+ age group. The overall mortality rate per attendance was 6.3%.The leading cause of death was cerebrovascular accident (CVA), followed by chronic renal disease and all types of pneumonia.Conclusion: The review of mortality patterns offers valuable insights into the epidemiology, outcomes, and challenges associated with emergency care. These findings underscore the importance of ongoing surveillance, quality improvement initiatives, and interdisciplinary collaboration to enhance patient care and inform health promotion strategies in communities aimed at reducing mortality.
Keywords: chronic pain.; biomarkers; opioid; opioid use disorder; neural alterations; Adults; Healthcare demand; Income inequalities; Propensity Score; Health Policy.; mortality; admissions; emergency department.; attendance; brought-in-dead